Improving post-EVAR surveillance with a smart stent-graft - Santos, Isa C. T. (2012)
Abdominal aortic aneurysms (AAA or triple A’s) are indolent and deadly diseases. Their treatment options involve either an invasive procedure or a minimally invasive one. When the minimally invasive procedure, endovascular aneurysm repair (EVAR), was introduced, it revolutionized the treatment of AAA’s due to advantages such as shortened hospital stays and reduced costs. As EVAR requires periodic imaging exams, questions are nowadays being raised regarding the procedure’s long-term cost-benefit relation. In order to reduce followup costs, new technological solutions are being pursued, namely EVAR stentgrafts with sensing capabilities. In this chapter, the suitability of aneurysm sac pressure measurement for EVAR surveillance is evaluated using an AAA computer model. In addition the design drivers underlying EVAR stent-grafts are reviewed and the development of a new flexible pressure sensor integrated into a stent-graft is described.